2021
DOI: 10.1109/access.2021.3057770
|View full text |Cite
|
Sign up to set email alerts
|

A Resampling Univariate Analysis Approach to Ovarian Cancer From Clinical and Genetic Data

Abstract: Ovarian cancer (OC) is the second most common gynecological malignancy and the gynecological tumor with the worst prognosis. To try to improve this situation, Data Science technologies could be a useful tool to help clinicians to know more about the disease. In our case, we are interested in exploring OC data to discover relationships between clinical and genetic factors and the disease progression. For it, we propose an analysis framework for simple and univariate statistical descriptions of features of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Dermoscopy is commonly used as a noninvasive skin imaging method for the detection of melanoma. Without any additional observation, the accuracy for identifying melanoma is higher by utilizing dermoscopy [5]. However, the diagnostic accuracy depends on the dermatologist's professional and experience skills.…”
Section: Introductionmentioning
confidence: 99%
“…Dermoscopy is commonly used as a noninvasive skin imaging method for the detection of melanoma. Without any additional observation, the accuracy for identifying melanoma is higher by utilizing dermoscopy [5]. However, the diagnostic accuracy depends on the dermatologist's professional and experience skills.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the growth of deep learning (DL) in the field of machine learning has greatly enhanced the performance of medical imaging. Several studies have shown the efficacy of classification-based DL, also known as image-based ML, which uses images as its primary input ( Bote-Curiel et al, 2021 , Chaki and Woźniak, 2023 , Chiu et al, 2022 , Dhini et al, 2022 , Saba et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%